Adolescent portraits : identity, relationships, and challenges - Garrod, Andrew; Smulyan, Lisa.; Powers, sally I; Kilkenny, Robert (Boston : Allyn and Bacon, 2005)
The 19 case studies written by college students for this supplemental psychology textbook illustrate the contemporary American teenage struggles with personal identity and wholeness, family and peer relationships, and unique crises and disabilities.-http://booksinprint.com.
Includes bibliographical references
Keywords: Adolescence -- Case studies; Adolescent psychology -- Case studies -- United States